Through analysis of sports activities methods to reduce injury - et. al. SulaуmanovSunnatulla, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This article analyzes the causes of injuries of professional athletes and amateur athletes, and proves that it is possible to mitigate the consequences of injuries for athletes through the effective organization of training, prevention of their injuries and the correct performance of pre-competition squats. Based on the results of observations and studies, recommendations were made to reduce sports injuries.